Me and you : britannica discovery library - Terracciano, Kezia (Encyclopaedia Britannica, Inc. Chicago, 2005)
This book focuses on the dynamics of relationships, emphasizing the importance of empathy and communication. It provides insights into building meaningful connections and understanding the perspectives of others.